Practical ethics for psychologists : a positive approach - Knapp, Samuel; Fingerhut, Randy (American Psychological Association, 2024)
"Guided by the APA Ethics Code and social justice, this book helps psychologists solve ethical dilemmas while empowering those impacted by their work"--